(untitled) (Academia Journal of Medicine, 2021)
Background Glaucoma remains a leading cause of irreversible blindness globally. While general population awareness studies exist, few have analysed the influence of prior interaction with eye care services through spectacle correction. Spectacle users theoretically have greater exposure to eye health education Objectives To compare the awareness and knowledge levels regarding glaucoma between spectacle users and non-spectacle users attending a tertiary care centre. Methods A hospital-based cross-sectional study was conducted from January 2021 to June 2021 in the Ophthalmology Outpatient Department (OPD) at Government Medical College Palakkad in Kerala. A total of 400 participants aged >40 years were recruited and divided into two groups: Group A (Spectacle Users, n=200) and Group B (Non-Spectacle Users, n=200). Data was collected using a pre-tested, structured questionnaire. Chi-square tests were used for statistical analysis. Results Awareness of glaucoma was significantly higher in Group A (62.5%) compared to Group B (21.5%) (p